Pendampingan Pencatatan dan Penyusunan Laporan Keuangan untuk Meningkatkan Transparansi dan Akuntabilitas Kelompok Tani Hutan Banyu Metu - Mia Lasmi Wardiyah (PT Cendekia Education Center, 2026)
This Community Service Program aimed to improve the capacity of the Banyu Metu Forest Farmers Group in recording and preparing financial reports to support transparency and accountability in group management. The program was conducted in Babakan Jaya Hamlet, Kedungwuluh Village, Padaherang District, using a participatory approach involving observation, training, practice, mentoring, and evaluation. The initial stage identified the group’s financial management conditions, followed by training on recording income and expenditures, classifying transactions, maintaining transaction evidence, and preparing simple financial reports. The results showed an improvement in participants’ ability to record transactions and prepare financial reports. The average participant competency increased from 42.5% before the program to 85.0% after mentoring, representing an increase of 42.5 percentage points. Practice-based mentoring helped participants understand the application of financial recording based on actual group transactions. The program contributed to strengthening the group’s capacity to produce more organized, understandable, transparent, and accountable financial information. Continuous financial recording is recommended to ensure the consistent implementation of the skills acquired through the program.